NEW EMBO MEMBER’S REVIEW: Nuclear interpretation of Dpp signaling in Drosophila - Affolter, Markus (Oxford University Press, 2001)
Signaling by Decapentaplegic (Dpp), a member of the TGFβ superfamily of signaling molecules similar to vertebrate BMP2 and BMP4, has been implicated in many developmental processes in Drosophila melanogaster. Notably, Dpp acts as a long-range morphogen during imaginal disc growth and patterning. Genetic approaches led to the identification of a number of gene products that constitute the core signaling pathway. In addition to the ligand-activated heteromeric receptor complex and the signal-transducing intracellular Smad proteins, Dpp signaling requires two nuclear proteins, Schnurri (Shn) and Brinker (Brk), to prime cells for Dpp responsiveness. A complex interplay between the nuclear factors involved in Dpp signaling appears to control the transcriptional readout of the Dpp morphogen gradient. It remains to be seen whether similar molecular mechanisms operate in the nucleus in vertebrate systems.